Mast seeding is stronger in taller plants - Qin, Haiming; Yi, Xianfeng (Frontiers in Plant Science, 2024)
Two economies of scale, predator satiation and pollination efficiency, have been proposed to explain the evolutionary mechanisms of mast seeding adopted by some long-lived plants. Plant height is strongly selected by pollination vectors and may also provide economies of scale; however, it remains unknown whether there is a close relationship between adult plant height and mast seeding intensity. Here, we analyzed mast seeding intensity of 158 plant species to test if adult plant height can select for mast seeding. We show that mast seeding intensities are higher in taller plant species irrespective of phylogeny, life form, pollination vector, and type of Spermatophytes.We also show that anemophily rather than entomophily selects for taller plant species and higher mast seeding intensities. The linear correlations and evolutionary links between adult plant height and mast seeding intensity provide evidence that mast seeding could have evolved as an adaptation to taller strategy of perennial plant species.